PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN KONSTRUKSI - Nur Evrina Wahyuni; Wiliyanti, Rizke; Nurhanifah, Afifa (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2025)
This study aims to analyze the effect of financial performance on stock prices through the components of Earnings per Share (EPS), Net Profit Margin (NPM), company size (SIZE), capital structure, and dividend policy. In this study, the data analysis used was multiple linear regression analysis with the classical assumption test previously performed as a condition for hypothesis testing. The samples used in this study are all construction sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2022 period with 36 observational data. The technique used in selecting the sample is the purposive sampling technique. The results showed that Earnings per Share (EPS), company size (SIZE), and dividend policy partially had a significant positive effect on stock prices. While the Net Profit Margin (NPM) and capital structure partially have no significant effect on stock prices.